Spectroscopic characterization of BPSCCO thin films grown by dip-coating technique - Carvalho, C. L.; Guedes, I (Elsevier B.V., 2003)
This work describes the growth of Bi2-xPbxSr2Can-1CunO2n+4 thin films by the dip-coating technique for 0.4 less than or equal to x less than or equal to 1. X-ray and Raman spectroscopic techniques were carried out in order to characterize the films at room temperature. From X-ray data it is observed that the films are multi-phased presenting phases 2201, 2212 and 2223 along with the undesirable Ca2PbO4 phase. It is also observed that phase 2212 becomes dominant when Pb content increases. The Raman modes observed agree with the overall features expected for these compounds. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: BPSSCO thin films; dip-coating technique; X-ray diffraction; Raman scattering